Non-linear finite element analysis of reinforced concrete deep beam with web opening - Ferry Alius; Bambang Piscesa; Faimun Faimun; Harun Alrasyid; Data Iranata (Institut Teknologi Sepuluh Nopember, 2020)
The use of Reinforced Concrete (RC) deep beams in building may requires web openings or holes for electrical and mechanical utilities passage. This web opening will change the behavior of RC deep beam and may resulted in early cracks even at service load. Hence, it is important to use a suitable tool to predict the full response of RC deep beam with opening. For that purpose, nonlinear finite element method using 3D-NLFEA software package which utilize a plasticity-fracture model is used to predict the behavior of RC deep beam. One deep beam specimen available in the literature is investigated. To study the effect of using structured and unstructured mesh, as well as different element types on the load deflection curve, hexahedral and tetrahedral solid element was used. From the comparisons, it was observed that the crack pattern between two different meshes was not similar. Structured mesh often has straighter crack propagation compared to the unstructured mesh. The load deflection curve for both models are similar and both models were performed satisfactorily in predicting the peak load of the deep beam.